Ex situ germplasm preservation and plant regeneration of a threatened terrestrial orchid, Caladenia huegelii, through micropropagation and cryopreservation - Bustam, B.; Dixon, Kingsley; Bunn, E. (2016)
Caladenia huegelii Rchb.f. is a threatened obligate mycotrophic orchid species with limited distribution in its remaining habitat, hence, this study to develop ex situ conservation protocols. An asymbiotic seed germination protocol was used to generate primary protocorms that were then used to proliferate secondary (adventitious protocorms). Both primary and secondary protocorms were utilised for development of a cryopreservation protocol. An average 94% germination of C. huegelii seeds occurred on ½ MS medium with 5% (v/v) coconut water) and 43% primary protocorms formed secondary (adventitious) protocorms) on ½ MS (– CW) + 5µM ∝-naphthaleneacetic acid + 2 µM BAP. Incubation at a constant 20 ± 0.5°C after cryopreservation significantly increased regeneration of both primary and secondary protocorms at 79 and 45%, respectively, compared with 46 and 19% at a higher, more variable standard culture temperature range (22-26°C). Seedlings were successfully regenerated from both cryopreserved primary and secondary protocorms, but only plantlets derived from primary protocorms were investigated for transfer to soil, where 88% plantlets survived, with sustained growth (average leaf length increase of 4.1 cm) after 12 weeks. This study demonstrates that plantlets derived from cryopreserved asymbiotically-produced protocorms can be established in soil and provide a feasible option to facilitate conservation and development of restoration protocols for endangered terrestrial orchids.